Kepercayaan Penyembuhan Jawa dan Jepang dalam Novel Pingkan Melipat Jarak - Nurmaulidia Nurmaulidia; Nasywa Azighotun Syahla; Muhammad Brian Apriansyah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This article discusses the phenomenon of healing beliefs in Javanese and Japanese culture which is presented through the narrative of the novel Pingkan Melipat Distance by Sapardi Djoko Damono. The novel explores the complexities of cross-cultural relationships, highlighting the traditional beliefs that influence the way the main character, Pingkan, deals with emotional and identity crises. In Javanese culture, healing beliefs are rooted in harmony between spirituality, nature and the body, while in Japanese culture, balance between the body, mind and environment is the main foundation. This article finds that through Pingkan's journey, this novel represents a cross-cultural dialogue that not only connects local and global values ​​but also opens up space for reflection on identity and healing in the modern era. With a literary approach and cultural perspective, this article presents an in-depth understanding of how healing traditions contribute to the sustainability of cultural values as well as being a tool to face the challenges of globalization.